The Effect Of Soybean Extract Nanoemulgel (Glycine max (L.) Merill) On The Number Of Fibroblasts In The Healing Process Of Traumatc Ulcers (In Vivo Study on White Wistar Rats) - Anjani, Fabela Artha; Feranisa, Anggun; Pratiwi, Rosa (Jurnal Medali, 2025)
Background: Traumatic ulcers are a common oral lesioncharacterized by epithelial damage caused by trauma. They can healspontaneously within 7-10 days but may develop into chronic ulcers ifuntreated. Current treatments like hyaluronic acid gels are effective but costlyand can cause hypersensitivity reactions. This study aimed to analyze the effectof soybean extract (Glycine max (L.) Merill) formulated as a nanoemulgel onfibroblast proliferation during traumatic ulcer healing.Method: An in vivo study using male Wistar rats was conducted. Thirty ratswere divided into five groups: nanoemulgel soybean extract at concentrationsof 50%, 60%, and 70%, a positive control group (hyaluronic acid gel), and anegative control group (gel base). Treatments were applied daily for five days,after which fibroblast proliferation was evaluated histologically. Statisticalanalyses included Shapiro-Wilk, Levene's test, One-Way ANOVA, and Posthoc tests.Results: The 50% nanoemulgel soybean extract group showed the highestfibroblast count among treatment groups, indicating its potential in promotingulcer healing. However, hyaluronic acid gel outperformed other groups.Variability in nanoemulsion preparation likely influenced the fibroblast count.Conclusion: Nanoemulgel soybean extract demonstrates promising effects onfibroblast proliferation in traumatic ulcer healing, particularly at 50%concentration. Despite limitations in preparation, the results highlight itspotential as an alternative to conventional treatments. Further studies shouldoptimize the formulation and assess its toxicity.